VIRTUAL UMRAH: ANTARA KEABSAHAN DAN PENGALAMAN SPIRITUAL - Rida Putri (Yayasan An-Nur Meunara Baro, 2025)
The emergence of Virtual Umrah, a digitally simulated pilgrimage experience, has sparked debate in the fields of Islamic jurisprudence and contemporary spirituality. This study aims to examine the legitimacy of Virtual Umrah from an Islamic legal perspective, explore users' spiritual experiences, and analyze responses from scholars and the public. Using a qualitative approach based on literature review and secondary data analysis, the study finds that Virtual Umrah cannot substitute for physical umrah, as it fails to fulfill essential legal requirements such as travel (safar) and actual ritual performance. Nonetheless, it holds significant potential as an educational tool to prepare and enhance spiritual awareness. Most users reported increased understanding and emotional connection to religious rituals, despite limitations in sensory and social interaction. Islamic scholars offer divergent views: some consider it a valuable tool for da’wah and learning, while others express concern over a potential dilution of sacred meaning. This study also emphasizes the need for religious guidelines and ethical frameworks to ensure that such innovations do not blur the distinction between symbolic worship and legally valid rituals. Given the rise of VR/AR technologies and the spiritual preferences of the digital generation, Virtual Umrah has the potential to become an effective educational bridge toward a more meaningful real-life pilgrimage experience.